Estrategias de enseñanza para el fortalecimiento de la educación inclusiva en la básica secundaria - Barreiro Novoa, Shirley Isabel; Oliveros Díaz, Daniela Esther; Solano Esparragoza, Zulma del Carmen (Revista Cedotic, 2024)
This research conducted an analysis of the inclusive education process in secondary schools in the department of Atlántico, identify strategies for the strengthening of inclusive education, based on the theoretical postulates of Booth, T. and M. Ainscow (2017), Godoy (2008), Cózar (2019), UNESCO (2019), National Ministry of Education (2017), among others. The research was oriented under the positivist paradigm, typified as projective, whose design is non-experimental, transectional, and field-based. The population consisted of teachers and directors of secondary basic education institutions in the Malambo (Atlántico); the sample was 106 teachers and 18 directors. Content validity was obtained by consulting the opinion of 7 experts, while reliability was calculated using the Cronbach’s Alpha coefficient. As a result, it was evidenced that the conditions of the schools, equal opportunities, and individualized attention showed a moderate behavior. Finally, it is recommended that the entire educational community should promote inclusive face-to-face and virtual environments where everyone can have access to the enjoyment of these